Vanishing act : the enduring mystery behind the legendary Doolittle raid over Tokyo - Hampton, Dan (St. Martin's Press, 2024)
"From New York Times bestselling author Dan Hampton comes the gripping, untold story of a vital secret mission set during the darkest days of the Second World War. In the dark days after the devastating Pearl Harbor attacks during the spring of 1942, the United States was determined to show the world that the Axis was not invincible. Their bold plan? Bomb Tokyo. On April 18, 1942, sixteen B-25s, known as the Doolittle Raiders, hit targets across Japan before escaping to China. The eighth plane, however, did not follow the other raiders. Instead, Plane 8's pilots, Captain Edward "Ski" York and Lieutenant Bob Emmens, never attacked Tokyo, but headed across Japan to the Soviet Union, supposedly due to low fuel. Yet, this bomber was the only plane on the mission with maps of the Soviet Union aboard. And why did Plane 8's route, recently discovered in the Japanese Imperial Archives, show them nowhere near their target? Uncovered facts reveal that bombing Tokyo was merely a cover for Plane 8's real mission, but what was their secret objective? No one, aside from the two pilots and whomever sent them on this mission, truly knew why they were there, nor has the reason ever been revealed. Until now. In Vanishing Act, for the first time, New York Times bestselling author and former fighter pilot Dan Hampton definitively solves the final mystery of the Doolittle Raid with never-before-published documents and photographs in exclusive collaboration with Japanese researchers and the Raiders' descendants"--